Signal of Rupiah Exchange Rate to US Dollar and Gross Domestic Product (GDP) - Vinsensius Vinsensius; Prihat Assih; Gaguk Apriyanto (JAFFA, 2020)
The purpose of this study is to analyse signal of rupiah/USD exchange rate and Indonesian Gross Domestic Products (GDP) towards Stock Price Composite Index. This study uses quantitative method. The data of research use quarterly time series data (January, April, July, October) starting from 2010 - 2018 obtained in the website of Bank Indonesia, Ministry of Commerce Republic Indonesia and Indonesia Stock Exchange. Data analysis method use Multiple Linear Regression, which findings of this study indicate that the rupiah/USD exchange rate gave a negative signal to the Stock Price Composite Index. In addition, the Indonesian Gross Domestic Products (GDP) gave a positive signal to the Stock Price Composite Index.